Historical Context for Development Virtual Reading Room as an Innovation at the Indonesia Open Universitys Library Services - Wahyono, Effendi (SUSURGALUR, 2015)
ABSTRACT: This paper intends to discuss the utilization of virtual reading room at the UT (Indonesia Open University), and the efforts to be addressed in order to improve student access on virtual reading room services. Data obtained from observations, during five months at UTâs library service on virtual reading room, were analyzed by using descriptive analysis. The findings indicated that the number of virtual reading room visitors, since its first launching in the third week of February 2012 until May 2012, reached a number of 21,437 visitors. Therefore, virtual reading room has been utilized by UTs students in looking for the learning materials in the need of their online tutorials and exams. The availability of learning materials, in the format of full text on virtual reading room, make studentâs problems in looking for learning materials can be solved. In order to improve student access on virtual reading room services, UTs libraries need to immediately upload all materials of UTs courses offered. Given the availability of learning materials related to the quality of student learning, it is recommended that there should be a research on the relationship between the utilization of virtual reading room and student learning outcomes.KEY WORD: Virtual reading room, innovation, library service, digital libraries, students of Indonesia Open University, and online tutorial and exam.IKHTISAR: âKonteks Historis untuk Pengembangan Ruang Baca Virtual sebagai Inovasi di Layanan Perpustakaan Universitas Terbuka Indonesiaâ. Tulisan ini bermaksud untuk membahas pemanfaatan ruang baca virtual pada UT (Universitas Terbuka) di Indonesia, dan upaya yang harus ditangani dalam rangka meningkatkan akses mahasiswa pada layanan ruang baca virtual. Data yang diperoleh dari pengamatan, selama lima bulan di layanan perpustakaan UT di ruang baca virtual, dianalisis dengan menggunakan analisis deskriptif. Temuan menunjukkan bahwa jumlah pengunjung di ruang baca dunia maya, sejak diluncurkan pertama pada minggu ketiga Februari 2012 hingga Mei 2012, mencapai angka 21,437 pengunjung. Oleh karena itu, ruang baca virtual telah dimanfaatkan oleh mahasiswa UT dalam mencari materi pembelajaran untuk kebutuhan tutorial online dan ujian. Ketersediaan bahan pembelajaran, dalam format teks penuh pada ruang baca virtual, membuat masalah mahasiswa dalam mencari materi pembelajaran dapat dipecahkan. Dalam rangka meningkatkan akses mahasiswa pada layanan ruang baca virtual, perpustakaan UT harus segera mengunduh semua bahan ajar UT yang ditawarkan. Mengingat ketersediaan bahan ajar yang berkaitan dengan kualitas pembelajaran mahasiswa, disarankan bahwa harus ada penelitian tentang hubungan antara pemanfaatan ruang baca virtual dengan hasil belajar mahasiswa.KATA KUNCI: Ruang baca virtual, inovasi, layanan perpustakaan, perpustakaan digital, mahasiswa Universitas Terbuka di Indonesia, serta tutorial secara online dan ujian.About the Author: Dr. Effendi Wahyono is Head of Library Center and Senior Lecturer at the Faculty of Social and Political Sciences UT (Indonesia Open University), Jalan Cabe Raya, Pondok Cabe, Pamulang, Tangerang Selatan 15418, Banten, Indonesia. For academic interests, the author can be contacted via e-mail at: effendi@ut.ac.idHow to cite this article? Wahyono, Effendi. (2015). âHistorical Context for Development Virtual Reading Room as an Innovation at the Indonesia Open Universitys Library Servicesâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.3(1), Maret, pp.99-112. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808. Â Chronicle of the article: Accepted (October 24, 2014); Revised (December 5, 2014); and Published (March 24, 2015).